PROPUESTA DE MEJORA EN EL PROCESO PRODUCTIVO DE HORCHATA PARA INCREMENTAR LA PRODUCTIVIDAD DE LA EMPRESA “LA SUREÑITA S.A.” - Córdova Encalada, Gabriela del Cisne (2024)
The objective of this research is to make a proposal to improve the production process of Horchata to increase the productivity of the company “La Sureñita S.A.” located in the Loja Canton of the Loja province. A qualitative approach was used based on the collection of information using the technique of direct observation and an interview with the production manager who explained the phases of the production process for the production of Horchata; likewise, a descriptive method was used where each of the times, resources and materials used in the manufacturing process were detailed; With the information collected, an analysis of the Lean Manufacturing tools was made, where two of them were selected and applied, the 5S and VSM (Value Chain Mapping), resulting in the implementation of the 5S that will allow the company to add red cards to classify what is unnecessary, checklist and yellow cards to get rid of unnecessary things that are within the production area, which will contribute to the improvement in the development of activities of the production process, likewise, a board of standards was placed for important communications. With the application of the VSM (Value Chain Mapping) we obtained as a result the identification of idle times and unnecessary movements in the production process for which when presenting the proposal we will obtain an optimization of time from 96 h: 58 min to 93 h: 13 min: 40 sec on a monthly basis.